Dampak Intellectual Capital Dan Capital Structure Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening - Ifa Fatimah Cahyani; Endah Tri Wahyuningtyas (Universitas Nahdlatul Ulama Surabaya, 2020)
This study is to determine the impact of intellectual capital, capital structure and company value by mediating financial performance. This study used secondary data, with purposive sampling method and data anilysis method using WarpPLS 6.0. Based on the results of this study, it shows that intellectual capital with VACA proxy has a significant positive impact on financial performance. Meanwhile, the VAHU proxy states that it has a significant negative effect on financial performance and measurement using STVA has a significant positive impact on financial performance. Capital structure using the debt to equity ratio indicator has a significant negative effect on financial performance. Intellectual capital with indicators VACA, VAHU, and STVA has a significant positive effect on firm value, capital structure has a positive impact on firm value, financial performance has a positive impact on firm value. Financial performance is able to mediate the relationship between VACA and STVA but not with VAHU and the capital structure.